Correlated Key Attributes for Sustainable and Universal Design: A Case Study through Meal Packaging in Thailand - Jarupan, Lerpong; Suriyong, Patcharawat (Naresuan University Journal: Science and Technology (NUJST), 2020)
The study reports results of a series of research efforts to examine congruence between two design principles: universal and sustainable design concepts. The methods mainly adopted the focus group interview and the survey. A paper tray for fried chicken was used as an illustrative case to test the design attributes drawn out. The findings of the first stage indicated that the packaging executives agreed that both universal and sustainable designs played important roles in the current packaging trends and could be considered as integrative design. With explicit concern by companies over economic and environmental benefits, the package should also facilitate ease of use by consumers but retain its integrity and functionality. The design strategy for package reduction at the end phase of use after product consumption, was pointed out. At the second stage, package designers’ points of view suggested the key design issues where consumer needs, environmental benefits and packaging functionality were all affected. At the final stage, responses to a questionnaire on the existing and proposed package designs for a fried chicken meal indicated that most consumers liked to use a paper tray for food products, despite the major problem of food leakage. The final findings indicated that the key structural factors of the proposed package with the correlated design attributes were easy handling and opening and facilitation of disposal. The extent of consumer satisfaction was subject to the right package structure and strength as well as clear information provided through graphics, pictures and symbols in order to provide guidance for disposal after use.  Keywords: Universal, Sustainable, Design attribute, Correlated, Packaging